Nonviolent conflict and civil resistance - Nepstad, Sharon Erickson; Kurtz, Lester R. (Research in social movements, conflicts, and change ;, 2012)
This special issue of Research in Social Movements, Conflicts and Change analyzes examples of nonviolent resistance from across the globe. It covers how regime changes, political movements and nonviolent unrest develop and then shape the political decisions of both civil society and the state. Section one is focused on the strategic interactions between nonviolent movements and the state. This includes discussions on the civil rights movement in Northern Ireland, youth movements in Post-Communist states and nonviolent Islamic movements in Turkey. The second and third sections examine regime conflicts and the global diffusion of nonviolent movements. Here chapters center on the Iranian Revolution, social psychological approaches to nonviolent civil resistance, the Palestinian human rights movements, the efforts of nonviolent INGOs and the Nashville civil rights movement. This volume is essential reading because it introduces new analytical concepts and theoretical frameworks for understanding nonviolent resistance, merging social movement scholarship with nonviolent studies in fresh and exciting ways.